2021
DOI: 10.1155/2021/6635225
|View full text |Cite
|
Sign up to set email alerts
|

Function and Mechanism of Novel Histone Posttranslational Modifications in Health and Disease

Abstract: Histone posttranslational modifications (HPTMs) are crucial epigenetic mechanisms regulating various biological events. Different types of HPTMs characterize and shape functional chromatin states alone or in combination, and dedicated effector proteins selectively recognize these modifications for gene expression. The dysregulation of HPTM recognition events takes part in human diseases. With the application of mass spectrometry- (MS-) based proteomics, novel histone lysine acylation has been successively disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 77 publications
(102 reference statements)
0
37
0
Order By: Relevance
“…Previous experiments have demonstrated that lactylation is an important PTM derived from lactate. The emergence of lactylation has improved our understanding of the function of lactate and its role in a variety of pathophysiological conditions 17,52 .For example, histone lactylation can directly promote gene transcription, and induce the polarization of macrophages from M1 to M2 16 .Lung myo broblasts promote the pro brotic activity of macrophages by inducing histone lactylation in the promoters of the pro brotic genes in macrophages 53 . Although some studies have shown that lactylation of histones plays an important role in transcription-related functional regulation, we need to further explore whether lactylation of nonhistone proteins matters and how it works.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have demonstrated that lactylation is an important PTM derived from lactate. The emergence of lactylation has improved our understanding of the function of lactate and its role in a variety of pathophysiological conditions 17,52 .For example, histone lactylation can directly promote gene transcription, and induce the polarization of macrophages from M1 to M2 16 .Lung myo broblasts promote the pro brotic activity of macrophages by inducing histone lactylation in the promoters of the pro brotic genes in macrophages 53 . Although some studies have shown that lactylation of histones plays an important role in transcription-related functional regulation, we need to further explore whether lactylation of nonhistone proteins matters and how it works.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature has revealed that there have been many types of PTMs of proteins (e.g., succinylation, crotonylation, 2-hydroxyisobutyrylation, malonylation, lactylation, and so on) ( 52 ), while most studies on glioma with seizure have focused on phosphorylation, which is the most common post-translational modifications of proteins. A study observed a dephosphorylation of KCC2 at residue Ser940 in a glioma model that exhibits hyperexcitability and the development of spontaneous seizures ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recent application of mass spectrometry-based proteomics identified novel histone lysine acylation including propionylation, butyrylation, 2-hydroxyisobutyrylation, β-hydroxybutyrylation, malonylation, succinylation, crotonylation, glutarylation, and lactylation [103]. Of these, lysine crotonylation is a recently described posttranslational modification [104], which adds a crotonyl group (CH 3 CH=CHCO 2 ) from crotonyl-CoA to lysine residues catalyzed by histone crotonylases [71].…”
Section: Other Histone Modificationsmentioning
confidence: 99%